The role of adiponectin in obesity-associated female-specific carcinogenesis. (October 2016) - Nagaraju, Ganji Purnachandra; Rajitha, Balney; Aliya, Sheik; Kotipatruni, Rama P.; Madanraj, Appiya Santharam; Hammond, Anthea; Park, Dongkyoo; Chigurupati, Srinivasulu; Alam, Afroz; Pattnaik, Subasini
Graphical abstract: Highlights: We review the association between obesity, adiponectin levels and female-specific malignances. We consider the role of adiponectin in the context of female-specific malignances. We discuss the potential of applying adiponectin as a therapeutic molecule for female-specific malignances. Abstract: Adipose tissue is a highly vascularized endocrine organ, and its secretion profiles may vary with obesity. Adiponectin is secreted by adipocytes that make up adipose tissue. Worldwide, obesity has been designated a serious health problem among women and is associated with a variety of metabolic disorders and an increased risk of developing cancer of the cervix, ovaries, uterus (uterine/endometrial), and breast. In this review, the potential link between obesity and female-specific malignancies is comprehensively presented by discussing significant features of the intriguing and complex molecule, adiponectin, with a focus on recent findings highlighting its molecular mechanism of action in female-specific carcinogenesis.